Composite catalyst for removing internal water from lignite and application of composite catalyst

By using lignite dewatering composite catalyst and combining precatalytic and ultrasonic reaction technology, the problems of large equipment investment, high energy consumption and serious moisture recovery in the lignite dewatering process in the existing technology have been solved, and the complete dewatering and efficient quality improvement of lignite has been achieved, reducing production costs and increasing the calorific value of coal.

CN119733560APending Publication Date: 2025-04-01SHANDONG SHUANGYUAN BIOTECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411926873.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing lignite dewatering technology has problems such as large investment in equipment, high energy consumption, high production costs, serious pollution, inability to completely destroy the functional groups of lignite, serious moisture reflux, low market price of coal powder after crushing, and low added value.

Method used

A lignite dewatering composite catalyst, including penetrant and solvent, is used to realize dewatering treatment of lignite through precatalysis and ultrasonic reactions. The catalyst consists of permeable agents such as JFC-M, JFC-2, JFC-6, and solvents such as polyethylene glycol 600, 1,2-propylene glycol, and is combined with a desiccant to form a composite catalyst mixture liquid for de-internal water treatment of lignite.

Benefits of technology

The complete dehydration of lignite is achieved, which avoids moisture reflux, reduces production costs, increases the heat generation of coal, and does not destroy the physical and chemical properties of lignite, and obtains high-quality lignite products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a composite catalyst for removing internal water from lignite and application thereof, and the composite catalyst comprises a composite catalyst mixed solution composed of a penetrant and a solvent, and also comprises a drying agent. The composite catalyst for removing internal water from lignite provided by the invention has relatively strong solubility and permeability, can catalyze lignite at normal temperature and normal pressure, adopts a method of assisting a drying agent, and has the advantages of thorough internal water removal, no moisture regaining and good effect, the treated lignite has low internal water content, the calorific value is averagely increased by more than 1200 kilocalories, and the content of internal water in the lignite is increased by more than 100 kilocalories. Meanwhile, other physical and chemical properties of the lignite are not damaged, and the lignite product is high in quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lignite dehydration, and in particular relates to a lignite dehydration composite catalyst and application thereof. Background Art

[0002] Lignite is a type of coal with the lowest degree of coalification. It is brown-black and dull, between peat and bituminous coal. It is formed by high temperature, high pressure and dehydration. The carbon content is generally between 60% and 77%, and the density is about 1.1-1.2g / cm 3 , the volatile components are greater than 40%, with the characteristics of high moisture content, high volatile components, easy weathering and fragmentation in the air, and low ignition point. Most lignite components are relatively complex, and the molecular structure is a complex mixture of various organic substances, including humic acid, humic acid, protein, sugar, etc.

[0003] Various organic matter and minerals contained inside and on the surface of lignite form channels with different pore sizes, such as blind holes, closed holes and open holes. Various pore structures give lignite the physical properties of developed pore structure, loose structure and large specific surface area, which provides sufficient space for the storage of moisture in lignite, making lignite have high moisture content and strong water absorption and moisture regain characteristics.

[0004] At present, lignite is mainly used as fuel for power plants. However, due to the low coalification degree of lignite, a large amount of black ash will float in the air when it is burned. If it is not treated by quality improvement, direct combustion will cause serious environmental pollution. At present, most of the following treatment methods are used in the world: rotary drying technology, belt drying technology, airflow drying technology, fluidized bed drying technology, vibration drying technology, and fuel technology.

[0005] Combining the above methods, there are mainly the following disadvantages:

[0006] 1. The equipment investment is large, the energy consumption is high (150-250℃ temperature), the production cost is high (200-350 yuan / ton), and the secondary pollution is serious; 2. The functional groups of lignite cannot be broken (no wall breaking). Even after drying, after being stored for a few days, the moisture regain phenomenon is serious, and the problem is not fundamentally and thoroughly solved; 3. Before the lignite is dehydrated, the coal must be crushed to 80-200 mesh before it can be used, resulting in high electricity consumption costs, difficult transportation, high freight and other problems; 4. The market price of the crushed coal powder is low, the added value of the product is low, and the economic benefits are poor.

[0007] The public patent application "A lignite additive and lignite dehydration method" (application number: CN201410329878.X) provides a lignite dehydration additive prepared with water and anionic surfactants, non-ionic surfactants, organic acids, water glass, carbonates and chloride compounds. The lignite is dehydrated by spraying the lignite dehydration additive, crushing, adding the lignite additive, and cold pressing to form honeycomb blocks, and finally drying. The disadvantage is that the coal needs to be crushed during the processing, which increases the processing cost on the one hand and affects the subsequent use of the processed coal on the other hand. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a composite catalyst for dehydrating lignite and its application, which can catalyze lignite to achieve the effect of dehydrating the lignite. The specific technical solution of the present invention is as follows.

[0009] In one aspect, the present invention provides a composite catalyst for dehydrating lignite, comprising a penetrant and a solvent;

[0010] The penetrant is selected from one of JFC-M, JFC-2, and JFC-6, or a combination of two or more components;

[0011] The solvent is selected from one of polyethylene glycol 600, 1,2-propylene glycol, ethylene glycol butyl ether, isopropanol, formamide, xylene, dichloromethane, toluene, ethylene glycol, methanol, ethanol, cyclohexanone, n-butanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, or a combination of two or more thereof.

[0012] Preferably, the composite catalyst for dehydrating lignite includes: JFC-M: 1-5 parts; ethylene glycol butyl ether: 10-15 parts; polyethylene glycol 600: 2-5 parts; methanol: 10-15 parts; isopropanol: 2-10 parts; and n-butanol: 5-10 parts.

[0013] Preferably, the composite catalyst for dehydrating lignite includes: JFC-2: 1-5 parts; ethylene glycol: 5-10 parts; toluene: 10-15 parts; ethanol: 5-10 parts; 1,2-propylene glycol: 10-15 parts; and cyclohexanone: 5-10 parts.

[0014] Preferably, the composite catalyst for dehydrating lignite includes: JFC-6: 1-5 parts; 1,2-ethylene glycol: 15-20 parts; formamide: 2-5 parts; dichloromethane: 10-15 parts; xylene: 5-10 parts; and cyclohexanol: 5-15 parts.

[0015] Preferably, a desiccant is also included, and the desiccant includes: one or a combination of two or more components of anhydrous calcium chloride, anhydrous magnesium sulfate, and calcium oxide; the preferred proportions are: anhydrous calcium chloride: 5-15 parts; anhydrous magnesium sulfate: 5-15 parts; calcium oxide: 5-10 parts.

[0016] When in use, the penetrant is dissolved in a solvent to obtain a composite catalyst mixed liquid, and the mass ratio of the composite catalyst mixed liquid to the desiccant is 1:3.

[0017] Preferably, the lignite is selected from the Ordos Minda coal yard.

[0018] Preferably, the composite catalyst mixture is prepared by the following method: dissolving 5 parts of the penetrant JFC-M in the following solvents: 5 parts of polyethylene glycol 600; 15 parts of ethylene glycol butyl ether; 10 parts of isopropanol; 15 parts of methanol; 10 parts of n-butanol;

[0019] Alternatively, 5 parts of the penetrant JFC-2 are dissolved in the following solvents: 10 parts of 1,2-ethylene glycol; 15 parts of toluene; 10 parts of ethanol; 15 parts of 1,2-propylene glycol; 10 parts of cyclohexanone;

[0020] Alternatively, 5 parts of the penetrant JFC-6 are dissolved in the following solvents: 20 parts of 1,2-ethylene glycol; 5 parts of formamide; 15 parts of dichloromethane; 10 parts of xylene; and 15 parts of cyclohexanol.

[0021] The reagent provided by the present invention has the following functions:

[0022] 1. Penetrant JFC-M is a surfactant. It is colorless and odorless, suitable for alkaline environments, and is an anionic penetrant. It is resistant to chemical environments, strong alkalis, strong acids, and hypochlorites, is easily soluble in water, has a moderate price, can dissolve quickly, and improves production efficiency.

[0023] 2. Penetrant JFC-2 is a surfactant. It is alkali-resistant and can maintain good penetration in an alkaline environment.

[0024] 3. Penetrant JFC-6 is a non-ionic surfactant, a colorless and transparent liquid with good water solubility and excellent permeability, especially in treating metal salts in deep hole crevices. It is resistant to hard water, acid and alkali, emulsification, water purification, and low temperature performance (such as minus 10 degrees) is still outstanding and will not solidify. These characteristics enable it to effectively treat functional groups (wall breaking) in lignite crevices and deep hole crevices, and play a good role.

[0025] 4. Ethylene glycol: It is a simple diol, a colorless, odorless, sweet liquid. It can be used as a solvent, antifreeze, and a phase transfer catalyst. It can dissolve inorganic salts such as calcium chloride, sodium chloride, zinc carbonate, zinc iodide, and potassium hydroxide. Due to its low molecular weight and active properties, it can cause esterification, etherification, alcoholization, oxidation, acetalization, dehydration and other reactions.

[0026] 5. Formamide: It is a colorless, transparent, oily liquid with a slight ammonia smell. It is hygroscopic and soluble. It also dissolves casein, glucose, corn starch, lignin, nylon, and some inorganic salts, copper, aluminum, zinc, tin, cobalt, iron, lead, etc., as well as some carbonic acid, nitric acid, etc. Formamide can undergo a variety of reactions. In addition to the three hydrogen atoms participating in the reaction, it can also undergo dehydration, COD removal, introduction of amino groups, introduction of acyl groups, and cyclization.

[0027] 6. Ethylene glycol butyl ether: It is an organic compound, a colorless and transparent liquid, easily soluble in water and product oil. It is a high boiling point solvent and is also used as an inactive diluent, wetting agent, dispersant, extractant, plasticizer, etc.

[0028] 7. Cyclohexanone: It contains carbonyl atoms, including saturated cyclic ketones within the six rings. It is a colorless, transparent liquid, slightly soluble in water, and soluble in most organic solvents such as alcohol, ether, and benzene. It can be used to dissolve fats, waxes, and rubber. It is a high-boiling point solvent and is usually mixed with a lower boiling point solvent to obtain a suitable evaporation rate and viscosity.

[0029] 8. Cyclohexanol: It is a colorless, transparent oily liquid or white needle-shaped crystals. It can be used as a solvent for metal soaps, oils, esters, and ethers.

[0030] 9. Isopropyl alcohol: It is a colorless and transparent liquid, easily soluble in water, and can also be dissolved in various organic solvents such as alcohol, ether, benzene, chloroform, etc. It has a stronger solubility for lipophilic substances than ethanol. It can be used as a solvent for alkaloids, an extractant, a dispersant, an antifreeze agent, etc.

[0031] 10. Polyethylene glycol 600: It is an almost colorless viscous liquid, or a translucent waxy soft substance. It has good water solubility and can be combined with many organic substances. It has good compatibility and has excellent lubricity, moisture retention, dispersibility, adhesion and other properties.

[0032] 11. Xylene: It is a colorless and transparent liquid with a special odor of aromatic hydrocarbons. It is used as a solvent, a synthetic monomer mixture, a component of high-alkyl gasoline, etc.

[0033] 12. 1,2-Propanediol: It is miscible with water, ethanol and a variety of organic solvents. It is a colorless viscous liquid under normal conditions, almost odorless, and slightly sweet. It is widely used as a desiccant, lubricant and solvent, softener, emulsifier, etc.

[0034] 13. Dichloromethane: It is a colorless, transparent liquid with an aromatic smell, slightly soluble in water, and is used as a solvent, extractant, mutagen, fire extinguisher, deesterification agent intermediate, etc.

[0035] 14. n-Butanol: It is a colorless and transparent liquid, used as a solvent, to adjust the evaporation rate and viscosity of the solvent, etc.

[0036] 15. Toluene: It is a colorless volatile liquid with a special aromatic smell, belonging to the aromatic hydrocarbons. It is easily soluble in ethanol, ether, and chloroform, but insoluble in water. It is suitable for spray paint, pesticides, benzoic acid, synthetic resins, polyester, etc. It can also be used as a solvent.

[0037] 16. 1,2-Ethylene glycol: It is the simplest diol, a colorless, odorless, sweet liquid, miscible with acetone, but less soluble in ether. It is used as a solvent. It is a phase transfer catalyst and also used for cell fusion. It has strong solubility and water absorption.

[0038] 17. Methanol: A colorless, transparent liquid used as a solvent and also used in organic synthesis. It can dissolve many inorganic salts.

[0039] 18. Ethanol: It is a kind of alcohol compound. It is a colorless and transparent liquid with an aromatic smell. It is an important organic solvent with the function of dehydration and decontamination. It is often used as fuel, disinfectant, solvent, etc.

[0040] 19. Anhydrous calcium chloride: It is a white crystal that is easily soluble in water. It releases a large amount of heat when dissolved and has strong hygroscopicity. It easily absorbs moisture from the air and is often used as a desiccant.

[0041] 20. Anhydrous magnesium sulfate: It is an inorganic compound that is soluble in water, ethanol, and glycerin, but insoluble in acetone. Because it absorbs water quickly and is a neutral compound that does not react chemically to various organic substances, it is often used as a desiccant.

[0042] 21. Calcium oxide: commonly known as quicklime. It is a white powder on the surface, and the impure one is grayish white. It has the function of absorbing water and SO2, and is often used as a desulfurization and desiccant.

[0043] Another aspect of the present invention provides an application of a composite catalyst for dehydrating lignite, specifically for dehydrating lignite.

[0044] As a third aspect of the present invention, the present invention further provides a method for dehydrating lignite, comprising the following steps:

[0045] 1. Material preparation process: The lignite is screened at multiple levels or the coal particles are classified by size.

[0046] 2. Pre-catalytic process section: transport the coal blocks of the same particle size classified in step 1 to the pre-catalytic reactor, add the diluted composite catalyst mixture into the pre-catalytic reactor and stir it to carry out the pre-catalytic reaction.

[0047] 3. The first process section of catalytic reaction and dehydration.

[0048] The coal after the pre-catalytic reaction is transported to the lignite dehydration ultrasonic reaction tank for the first dehydration treatment. After the reaction is carried out under the conditions of 14-35 Hz frequency and ultrasonic time of 10-30 minutes, it enters the catalytic and drying reaction tank;

[0049] 4. Catalytic reaction and dehydration second process section: The coal treated with the composite catalyst mixture and ultrasonic wave is transported from the ultrasonic reaction tank to the catalytic and drying reaction tank through a stainless steel, perforated screen belt conveyor, and a desiccant is added to continue the reaction;

[0050] 5. Coal washing process: The coal after the reaction in the catalytic and drying reaction tank is transported to the coal washer and washed with water;

[0051] 6. Solid-liquid separation and filtrate recycling process section: After the coal washing process section is completed, the lump coal is sorted and transported to the yard by a belt conveyor for natural air drying for standby use; a small amount of coal slime is separated into solid and liquid by a plate and frame filter press, and the water after solid-liquid separation is pumped into the catalytic and drying reaction tank for recycling, and the coal after solid-liquid separation is transported to the next process section by a belt conveyor;

[0052] 7. Residual composite catalyst and desiccant recovery process section: The composite catalyst remaining in the coal is evaporated, and the evaporated steam is pumped into the condenser for condensation recovery;

[0053] 8. Drying: The coal after solid-liquid separation is dried to obtain the finished product.

[0054] Preferably, in step 3 and step 4, the mass ratio of the composite catalyst mixture to the desiccant is 1:3.

[0055] Furthermore, the amount of the composite catalyst mixture added before dilution is 5 kg / ton of coal; the amount of the desiccant added is 15 kg / ton of coal.

[0056] The process flow and application method of the present invention described above have the following advantages:

[0057] 1. The present invention provides a composite catalyst for dehydrating lignite and an application method thereof. The composite catalyst for dehydrating lignite provided by the present invention has strong solubility and permeability, and can catalyze lignite at room temperature and pressure. By using a method assisted by a desiccant, the present invention removes internal water thoroughly without moisture regain, and has a good effect. The water content of the treated lignite is low, and the calorific value is increased by an average of more than 1,200 kcal. At the same time, other physical and chemical properties of the lignite are not destroyed, and a high-quality lignite product is obtained.

[0058] 2. The composite catalyst of the present invention is neutral, does not use strong alkali, strong acid, or prohibited chemical reagents, is non-corrosive, colorless, odorless, non-toxic, and has no secondary pollution. The chemical reagents used are easy to purchase and inexpensive.

[0059] 3. The present invention has the advantages of short process flow, no expensive equipment, easy-to-purchase equipment, all domestic equipment, low price, low solid investment, easy maintenance, and is suitable for large-scale production lines.

[0060] 4. No need to crush to (80-200 mesh), the catalyst can be directly sprayed on the coal after classification and screening to carry out catalytic reaction.

[0061] 5. After the reaction is completed, use a rotary drum dryer at 120 degrees to 150 degrees to dry.

[0062] 6. After the composite catalyst and catalytic reaction, the coal will rupture the cell wall inside the lignite, so that all the water inside will overflow, and some metal salts in the network structure will be degraded without causing moisture reappearance.

[0063] 7. The quality of lignite is improved through dehydration treatment, and the calorific value is increased (calorific value 1000-1500 kcal).

[0064] 8. The production cost is low, the floor space is small, and it has good economic and social benefits.

[0065] 9. Green, low-carbon, environmentally friendly, energy-saving, emission-reducing, and high resource utilization. It is particularly suitable for the quality improvement of low-calorie lignite and the treatment of tailings ponds.

[0066] 10. This technology does not require crushing during the processing process and can be applied to the processing of wider coal diameters. Since the coal diameter after processing is large, it can be transported over long distances using ordinary vehicles. The processed coal has a wide range of uses and is suitable for various purposes. DETAILED DESCRIPTION

[0067] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0068] The present invention provides a method for removing water from lignite, comprising the following steps:

[0069] 1. Material preparation process section:

[0070] After the lignite is screened through multiple stages, the gangue in the coal is removed, and then it is transported to the metering bin by conveyors according to different particle sizes, thus completing the material preparation process.

[0071] 2. Pre-catalytic process section:

[0072] The coal prepared in step (i) is weighed by an electronic scale and conveyed to a mixer by a belt conveyor, and a diluted mixture of the composite catalyst and water is added at the same time. The dilution process of the composite catalyst is to dilute it once in advance with water at a ratio of 1.0:5.0 times by weight, and then dilute the once diluted liquid twice with 200 times by weight of water using a high-pressure metering pump.

[0073] According to the weight ratio of lignite to the diluted composite catalyst of 10:1.0, a high-pressure metering pump is used to spray the dilution liquid into the mixer at one time to fully mix the lignite and the composite catalyst dilution liquid (mixing time is 15 minutes) and then transport them to the ultrasonic reaction tank with a screw conveyor. The pre-catalytic reaction is completed. The weight ratio of lignite to the diluted composite catalyst is preferably 10:2.0.

[0074] 3. Catalytic reaction and dehydration (I) process section:

[0075] The lignite after the mixed pre-catalytic reaction is transported to the lignite desulfurization (I) ultrasonic reaction tank by a belt conveyor, and the ultrasonic wave is turned on for catalytic reaction (ultrasonic wave between 14 Hz and 25 Hz, ultrasonic wave time is 10-15 minutes) for 60 minutes. After the reaction is completed, it is transported to the next process section through the porous sieve-shaped stainless steel conveyor of the ultrasonic reaction tank. During the transportation process, the filtered water is directly pumped back to the ultrasonic reaction tank for use by a pump, thus completing the catalytic reaction.

[0076] 4. Catalytic reaction and dehydration (II) process section:

[0077] The coal after the catalytic reaction is completed is transported to the desiccant reaction tank through the ultrasonic reaction tank and the stainless steel transfer belt with a porous screen, and the measured desiccant is added at the same time. The added amount is based on the weight ratio of the lignite to the desiccant (10:0.2-0.5). The reaction time is 60 minutes. After 60 minutes, the lignite is conveyed to the coal washing process section through a belt conveyor, completing the catalytic reaction and dehydration (II) reaction process section.

[0078] 5. Coal washing process section:

[0079] The lignite after catalytic reaction, internal water removal and drying reaction is transported to the coal washing machine by a belt conveyor. The internal water and lignite functional groups in the process of catalytic reaction, internal water removal and drying reaction are broken and dried. Then, washing is carried out (mainly to wash away the gangue, ash water and part of the sulfur in the lignite) to ensure that the quality of the lignite meets the standards, and the coal washing process is completed.

[0080] 6. Solid-liquid separation and filtrate recycling process section:

[0081] The washed coal is transported to the storage yard by a belt conveyor. The washed coal slurry is then pumped to the plate and frame machine by a mud pump for filter pressing and solid-liquid separation. The coal after solid-liquid separation is transported to the next process section (section 7) by a belt conveyor. The separated filtrate is pumped to the sedimentation tank for filtration treatment, and then pumped to the desiccant reserve tank. (After sampling and testing before use, the desiccant content in the filtrate is determined. According to the technical indicators, it is replenished with fresh desiccant once and then recycled. The ratio with coal remains unchanged during use, and the solid-liquid separation and filtrate recycling process section are completed.

[0082] 7. Drying and residual desiccant recovery process section:

[0083] The coal separated from solid and liquid is conveyed to the drum dryer by a belt conveyor, and the heating system is turned on to control the temperature between 120-150 degrees to evaporate the desiccant and a small amount of composite catalyst remaining in the lignite. The evaporated steam is pumped into the condenser for condensation recovery (because the residual composite catalyst and desiccant content is negligible and will not affect the recycling, so considering the recovery cost, there is no need to recover them separately), and the recovery process of composite catalyst and desiccant is completed.

[0084] Embodiment 1, the main equipment for dehydrating lignite of the present invention comprises:

[0085] Raw material bin, belt conveyor, electronic weighing bin, mixer, pre-catalytic reactor, catalytic dehydration ultrasonic reaction tank, catalytic and drying reaction tank, coal washer, plate and frame filter press, dryer, each device is connected by a screw conveyor or belt conveyor.

[0086] The pre-catalytic reactor used in this embodiment adopts a conventional reactor with a stirring device; the catalytic dehydration ultrasonic reaction tank adopts an ultrasonic reactor; the catalytic and drying reaction tank can adopt conventional steam drying equipment, and its structure is not limited.

[0087] The present invention adopts the following lignite dehydration process:

[0088] The lignite is transported from the raw material bin to the electronic weighing bin via a belt conveyor, and then transferred to a mixer after weighing, sprayed with a diluted composite catalyst aqueous solution, and then sent to a pre-catalytic reactor via a conveyor. After the pre-catalytic reaction, it is transferred to a catalytic dehydration ultrasonic reaction tank for reaction, and a desiccant is added for reaction, and then transported to a catalytic and drying reaction tank. After the catalytic and drying reactions, the coal is transported to a coal washer for washing, and then transported to a plate and frame filter press by a belt conveyor for solid-liquid separation. The solid is transported to a dryer by a belt conveyor for drying to obtain a product.

[0089] Through the catalytic dehydration ultrasonic reaction tank, the catalytic reaction in the catalytic and drying reaction tanks can improve the dehydration effect.

[0090] Example 2, a composite catalyst for dehydrating lignite.

[0091] In one embodiment, the composite catalyst components used are: JFC-M: 5 parts; ethylene glycol butyl ether: 15 parts; polyethylene glycol 600: 5 parts;

[0092] Methanol: 15 parts; isopropanol: 10 parts; n-butanol: 10 parts.

[0093] In one embodiment, the composite catalyst components used are: JFC-2: 5 parts; ethylene glycol: 10 parts; toluene: 15 parts; ethanol: 10 parts; 1,2-propylene glycol: 15 parts; and cyclohexanone: 10 parts.

[0094] In one embodiment, the composite catalyst components used are: JFC-6: 5 parts; 1,2-ethylene glycol: 20 parts; formamide: 5 parts; dichloromethane: 15 parts; xylene: 10 parts; and cyclohexanol: 15 parts.

[0095] Desiccant: anhydrous calcium chloride: 15 parts; anhydrous magnesium sulfate: 15 parts; calcium oxide: 10 parts. Use one or more of the above desiccants.

[0096] The mass ratio of the composite catalyst to the desiccant is 1:3.

[0097] 1. First, add the penetrant and solvent of the lignite dehydration composite catalyst into the composite stirred reactor in accordance with the weight ratio.

[0098] 2. Store the prepared lignite dehydration composite catalyst for 1-2 hours before use.

[0099] 3. Desiccant, because of its strong water absorption and active nature, cannot be compounded in advance. It can be directly mixed and used on the production line according to the weight ratio.

[0100] 4. After lignite is screened, remove impurities such as gangue from the coal. It is transported to the raw material bin through a belt conveyor, and then transported to the electronic weighing bin through a belt conveyor. Turn on the electronic scale and measure it into the mixer in proportion. At the same time, the pre-prepared lignite dehydration composite catalyst is diluted with 1:5 times the weight of water for a one-time dilution. Then, the dilution is diluted twice with a high-pressure metering pump at a weight ratio of 5 kg of composite catalyst liquid: 1000 kg of coal, and then sprayed into the lignite. The ratio of raw coal to dilution is 10:2.0 by weight. After being fully mixed in the mixer, it enters the lignite dehydration pre-catalytic reactor through a conveyor, and the agitator is turned on at the same time. After 60 minutes of pre-catalytic reaction, it enters the lignite dehydration (I) ultrasonic reaction tank.

[0101] 5. After the pre-catalytic reaction, the lignite is transported to the lignite dehydration ultrasonic reaction tank, and the ultrasonic wave is turned on. The ultrasonic wave is 14-25 Hz and the reaction time is 10-30 minutes. After the ultrasonic wave is completed, before entering the lignite dehydration (II) catalytic and drying reaction tank, (the water filtered by the stainless steel mesh belt machine of the ultrasonic reaction tank can be pumped back to the ultrasonic reaction tank for recycling), and at the same time, anhydrous calcium chloride desiccant (15 kg / ton of coal) is added to the ultrasonic reaction tank in a one-time manner according to the weight ratio. After the reaction time is 30 minutes, it enters the dehydration process section.

[0102] 6. Use a screw conveyor to transport the coal after the catalytic and drying reaction to the coal washer, where the lignite is further catalyzed and dried, and the impurities after the reaction are washed out to achieve the goal of improving the quality and efficiency of the lignite.

[0103] 7. The washed lignite is screened out with large particles by grading, and then transported to the yard by belt conveyor. A small part of the coal slurry is pumped into the plate and frame filter press by mud pump for solid-liquid separation. The filtrate after separation is pumped into the sedimentation tank and recycled after simple filtration. The residue (the content of desiccant) in the circulating water should be tested before use, and new desiccant should be added once according to the test results and then recycled. The content of composite catalyst is small and negligible, and will not affect the next drying.

[0104] 8. After solid-liquid separation, the coal is conveyed to a drum dryer by a belt conveyor. Under the condition of 120-150 degrees, the composite catalyst remaining in the coal is evaporated by evaporation, and the evaporated steam is pumped into a condenser for condensation recovery. The recovered liquid is pumped into the circulating water storage tank in step (7), and recycled after detection and treatment. The coal is required to be dried to a moisture content of less than 2.0-3.5. The coal undergoes pre-catalytic reaction, catalytic dehydration (I) reaction, catalytic dehydration (II) reaction, coal washing reaction, solid-liquid separation, wastewater recovery, drying, etc., and high-quality lignite is obtained in the process stage.

[0105] Example 3, lignite decatalytic treatment method:

[0106] Composite catalyst: JFC-M: 5 parts; ethylene glycol butyl ether: 15 parts; polyethylene glycol 600: 5 parts; methanol: 15 parts; isopropanol: 10 parts; n-butanol: 10 parts. Desiccant: anhydrous calcium chloride: 15 parts; anhydrous magnesium sulfate: 15 parts; calcium oxide: 10 parts. One or more desiccants. The sum of the weight ratios of the above composites is 100%. Specific operation method:

[0107] 1. First, add the chemical reagents in the lignite dehydration composite catalyst into the reactor in order of weight ratio and chemical properties.

[0108] 2. Add the penetrant JFC-M, then add ethylene glycol butyl ether in order, and turn on the mixer. After confirming that all the dilution is complete, add polyethylene glycol 600 and methanol, and turn on the mixer. After the polyethylene glycol 600 and methanol are completely diluted, add isopropanol and n-butanol in order. Let it stand for 30 minutes and set aside.

[0109] 3. Desiccant is not suitable for pre-mixing due to its strong water absorption. It should be prepared in production according to the required weight ratio.

[0110] 4. This example uses lignite (coal powder) for testing.

[0111] 5. After the lignite in the spare bin is weighed with an electronic scale, it is transported to the mixer by a belt conveyor for mixing. When entering the mixer, the pre-compounded catalyst is first diluted with water of the same weight. Then, the one-time dilution is diluted twice with a high-pressure metering pump according to the weight ratio of 5 kg of composite catalyst dilution: 1000 kg of water. Then, it is sprayed on the coal with a high-pressure metering pump to make it uniform.

[0112] 6. After being mixed evenly, the coal is conveyed to the pre-catalytic reactor by a belt conveyor, and the mixer is turned on for 30 minutes of pre-catalytic reaction. Then it is conveyed to the lignite dehydration (I) ultrasonic reaction tank by a belt conveyor, and the ultrasonic wave is turned on (10-25 Hz, reaction time is 30 minutes), and then it is conveyed to the lignite dehydration and drying (II) reaction tank by an ultrasonic stainless steel mesh conveyor, and a desiccant, 15 kg of calcium chloride, is added at one time. After the reaction time is 30 minutes, it enters the coal washer. After the coal washing is completed, the large pieces of coal are conveyed to the yard by a belt conveyor for standby use. The coal sludge is pumped into the plate and frame filter press by a mud pump, and the coal sludge filtered out is conveyed to the dryer by a belt conveyor for drying (analytical water: 2.0-3.5), and the dried coal is ready for use.

[0113] Example 4, lignite dehydration treatment method:

[0114] 1. Composite catalyst:

[0115] JFC-2: 5 parts; ethylene glycol: 10 parts; toluene: 15 parts; ethanol: 10 parts; 1,2-propylene glycol: 15 parts; cyclohexanone: 10 parts.

[0116] Desiccant: anhydrous calcium chloride: 15 parts; anhydrous magnesium sulfate: 15 parts; calcium oxide: 10 parts or a mixture of the above.

[0117] 2. Specific operation methods:

[0118] 1. First, compound the chemical reagents in the composite catalyst according to their properties and the required weight percentage.

[0119] 2. Based on the dilution characteristics of ethylene glycol, toluene and ethanol, add them to the compounding reactor first, add methanol according to the required weight percentage, then add JFC-2 permeability according to the required weight percentage, and turn on the stirrer to stir and dilute. After ensuring complete dilution, add 1,2-propylene glycol and cyclohexanone, continue stirring for 30 minutes, and then let it stand for 60 minutes for use.

[0120] 3. Desiccant, because of its strong water absorption, should be prepared and used on the actual production line according to the required weight percentage.

[0121] 4. This example uses (lump coal) for the experiment.

[0122] 5. Take 10 tons of lignite lumps, first dilute the composite catalyst prepared in step (3) with 10 times the weight of water, and then use a high-pressure metering pump to dilute the diluted solution for a second time according to the weight ratio of 5 kg of composite catalyst dilution solution to 1000 kg of water. The high-pressure metering pump sprays the lignite lumps and the diluted composite catalyst on the lignite lumps in a weight ratio of 1:1. After being fully mixed in a mixer, the mixture is conveyed by a belt conveyor to the lignite de-internalization (I) ultrasonic reaction tank (reaction time is 30 minutes, at 14-25 Hz, ultrasonic 10-30 minutes), and then conveyed to the lignite de-internalization (II) drying reaction tank by an ultrasonic stainless steel porous conveyor, and 10 kg of desiccant calcium oxide is added. After reacting for 30 minutes, the mixture is conveyed to the storage yard by a belt conveyor for natural air drying for standby use. A small amount of coal sludge is pumped to the plate and frame filter press by a mud pump for solid-liquid separation. The separated coal is transported to the dryer by a belt conveyor for drying. The analytical water content of the treated coal is required to be less than 2.0-3.5. The wastewater from solid-liquid separation is pumped to the ultrasonic reaction tank for recycling in the lignite degassing (I) ultrasonic reaction tank and the lignite degassing (II) drying reaction tank. The water from the plate and frame filter press is pumped to the condenser for condensation treatment. The condensed water is pumped to the lignite degassing water, which is then diluted in the composite catalyst or in the ultrasonic reaction tank for recycling, thus completing the catalytic reaction.

[0123] Example 5, dehydration treatment of lignite.

[0124] 1. Composite catalyst: JFC-6: 5 parts; 1,2-ethylene glycol: 20 parts; formamide: 5 parts; dichloromethane: 15 parts; xylene: 10 parts; cyclohexanone: 15 parts.

[0125] Desiccant: anhydrous calcium chloride: 15 parts; anhydrous magnesium sulfate: 15 parts; calcium oxide: 10 parts, one or more desiccants.

[0126] The sum of the weight ratios of the above composites is 100%.

[0127] 2. Specific operation methods:

[0128] 1. First, add the chemical reagents in the composite catalyst for dehydrating lignite into the reactor in accordance with the weight ratio and chemical properties and in order for compounding.

[0129] 2. According to the chemical properties of JFC-6; 1,2-ethylene glycol, first add the above two reagents into the reactor and stir (20 minutes), then add formamide, dichloromethane, xylene and cyclohexanone 20 minutes later. Continue stirring for 30 minutes, and after ensuring complete dilution, let it stand for 60 minutes for use.

[0130] 3. Desiccant, because of its strong water absorption, should be prepared and used immediately on the production line according to the required weight ratio.

[0131] 4. In this implementation 3, lignite raw coal was used for the experiment.

[0132] 5. Take 10 tons of raw lignite coal, first dilute the composite catalyst prepared in step (2) with 10 times the weight of water, and then dilute the diluted liquid with a high-pressure metering pump according to the weight ratio of 5 kg of the composite catalyst dilution liquid to 1000 kg of water. Use a high-pressure metering pump to spray the raw coal and the diluted composite catalyst on the raw coal in a weight ratio of 1:1. After fully mixing in a mixer (time is 15 minutes),

[0133] Then it is conveyed by belt conveyor to the ultrasonic reaction tank for lignite dehydration (I) (reaction time is 60 minutes, at 14-25 Hz, ultrasonic time is 10-30 minutes), and then the lignite after reaction is conveyed to the drying reaction tank for lignite dehydration (II) by ultrasonic stainless steel porous conveyor, and 15 kg of anhydrous magnesium sulfate is added as desiccant at the same time. After the reaction time is 30 minutes, the large-size coal is separated by screening and conveyed to the yard by belt conveyor for natural air drying. A small part of the coal sludge is pumped into the plate and frame filter press by mud pump for solid-liquid separation. The separated lignite is conveyed to the dryer by belt conveyor for drying treatment (temperature controlled at 120-150 degrees). The moisture content of the treated coal is required to be below (analyzed water: less than 2.0-3.5). The dried raw coal is put into storage for use after passing the inspection. The solid-liquid separation wastewater is transported from the lignite dehydration (I) ultrasonic reaction tank to the lignite catalytic and drying dehydration (II) reaction tank. The water filtered by the stainless steel mesh belt conveyor is pumped back to the ultrasonic reactor for recycling. The water from the plate and frame filter press is pumped into the condenser for condensation treatment. The condensed water is pumped into the composite catalyst dilution tank or the ultrasonic reaction tank for recycling, thus completing the dehydration of the lignite raw coal.

[0134] Test example: Parameter comparison table of different lignite (coal powder, lump coal, raw coal) before and after treatment:

[0135] Experimental data on lignite quality improvement using composite catalyst

[0136] 1. Take coal samples from Minda Coal Yard in Ordos, Inner Mongolia (original results):

[0137] The inspection results of irregular pulverized coal at the coal yard are shown in Table 1.

[0138] Coal sample original test data:

[0139]

[0140] 2. Test data of coal sample after crushing before experiment Test data of raw coal after crushing (80 mesh coal powder)

[0141]

[0142] 3. Test results of composite catalyst quality improvement

[0143]

[0144] The lump coal is the test result of the product after the process provided in this application, and then the product coal is tested for stability after quality improvement (rehumidification conditions: relative humidity 90%, placed for 24 hours) product test results.

[0145] The method provided by the present invention is used for lignite desulfurization and upgrading, and the internal water content of the coal is reduced to below 2.0, and the sulfur content is also reduced (65-70% of the original sulfur content).

[0146] The present invention can break the functional groups of lignite under normal pressure and temperature without heating, and make the desiccant penetrate into the internal structure of lignite, thereby realizing the complete removal of the internal water of lignite. The greatest advantage is that it does not regain moisture and does not damage the physical and chemical properties of lignite. The ash and sulfur contents are reduced, and the calorific value of lignite is increased by 1000-1500 kcal, bringing good environmental benefits, economic benefits, and social benefits.

[0147] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite catalyst for dehydrating lignite, characterized in that: Includes penetrants and solvents; The penetrant is selected from one of JFC-M, JFC-2, and JFC-6, or a combination of two or more components; The solvent is selected from polyethylene glycol 600, 1,2-propylene glycol, ethylene glycol butyl ether, isopropanol, formamide, xylene, dichloromethane, toluene, ethylene glycol, methanol, ethanol, cyclohexanone, n-butanol, cyclohexanol, 1,2-ethylene glycol, 1,2-propylene glycol, or a combination of two or more components.

2. The composite catalyst for dehydrating lignite according to claim 1, characterized in that: The composite catalyst for dehydrating lignite includes: JFC-M: 1-5 parts; Ethylene glycol butyl ether: 10-15 parts; Polyethylene glycol 600: 2-5 parts; Methanol: 10-15 parts; Isopropyl alcohol: 2-10 parts; n-Butanol: 5-10 parts.

3. The composite catalyst for dehydrating lignite according to claim 1, characterized in that: The composite catalyst for dehydrating lignite includes: JFC-2: 1-5 parts; ethylene glycol: 5-10 parts; Toluene: 10-15 parts; Ethanol: 5-10 parts; 1,2-propylene glycol: 10-15 parts; Cyclohexanone: 5-10 parts.

4. The composite catalyst for dehydrating lignite according to claim 1, characterized in that: The composite catalyst for dehydrating lignite includes: JFC-6: 1-5 parts; 1,2-ethylene glycol: 15-20 parts; Formamide: 2-5 parts; Dichloromethane: 10-15 parts; Xylene: 5-10 parts; Cyclohexanol: 5-15 parts.

5. The composite catalyst for dehydrating lignite according to claim 1, characterized in that: It also includes a desiccant, which includes one or a combination of two or more components: anhydrous calcium chloride, anhydrous magnesium sulfate, and calcium oxide.

6. The composite catalyst for dehydrating lignite according to claim 1, characterized in that: The composite catalyst mixture was prepared by the following method: 5 parts of the penetrant JFC-M were dissolved in the following solvents: 5 parts of polyethylene glycol 600; 15 parts of ethylene glycol butyl ether; 10 parts of isopropanol; Methanol: 15 parts; n-butanol: 10 parts; Alternatively, dissolve 5 parts of the penetrant JFC-2 in the following solvents: 1,2-ethylene glycol: 10 parts; toluene: 15 parts; ethanol: 10 parts; 1,2-propylene glycol: 15 parts; cyclohexanone: 10 parts; Alternatively, dissolve 5 parts of penetrant JFC-6 in the following solvents: 20 parts of 1,2-ethylene glycol; 5 parts of formamide; Dichloromethane: 15 parts; xylene: 10 parts; cyclohexanol: 15 parts.

7. An application of a composite catalyst for dehydrating lignite, characterized in that: Used for dehydrating lignite.

8. A method for dehydrating lignite, characterized in that: The steps include: Step 1, material preparation process section: lignite is screened at multiple levels or the coal particle size is classified according to size; Step 2, pre-catalytic process section: transport the coal blocks of the same particle size classified in step 1 to the pre-catalytic reactor, add the diluted composite catalyst mixture into the pre-catalytic reactor, and stir at the same time to carry out the pre-catalytic reaction; Step 3, catalytic reaction, dehydration first process section: The coal after the pre-catalytic reaction is transported to the lignite dehydration ultrasonic reaction tank for the first dehydration treatment. After the reaction is carried out under the conditions of 14-35 Hz frequency and ultrasonic time of 10-30 minutes, it enters the catalytic and drying reaction tank; Step 4, catalytic reaction, dehydration second process stage: the coal treated with the composite catalyst mixture and ultrasonic wave is transported from the ultrasonic wave reaction tank to the catalytic and drying reaction tank, and a desiccant is added to continue the reaction; Step 5, coal washing process: the coal after the reaction in the catalytic and drying reaction tank is transported to the coal washer and washed with water; Step 6, solid-liquid separation and filtrate recycling process section: the coal after the coal washing process section is sorted and the lump coal is transported to the yard by a belt conveyor for natural air drying for standby use; the coal slime is separated into solid and liquid by a plate and frame filter press, and the water after solid-liquid separation is pumped into the catalytic and drying reaction tank for recycling, and the coal after solid-liquid separation is transported to the next process section by a belt conveyor; Step 7, residual composite catalyst and desiccant recovery process section: the composite catalyst remaining in the coal is evaporated, and the evaporated steam is pumped into a condenser for condensation recovery; Step 8, drying: drying the coal after solid-liquid separation to obtain a finished product.

9. The method for dehydrating lignite according to claim 8, characterized in that: In step 3 and step 4, the mass ratio of the composite catalyst mixture to the desiccant is 1:

3.

10. The method for dehydrating lignite according to claim 8, characterized in that: The amount of the composite catalyst mixture added before dilution is 5 kg / ton of coal; the amount of the desiccant added is 15 kg / ton of coal.

Citation Information

Patent Citations

  • A kind of lignite additive and lignite dehydration treatment method

    CN104073319B